Extent of Applicability of Offline Mobile Application for Modules and Learning Packets - Ahillon Jr., Ricardo Cruz; Aquino, Paulo Martin M. (Bumi Publikasi Nusantara, 2024)
The current challenge faced by schools in returning to the traditional 5-day school week stems from various factors such as limited classroom availability, a shortage of educators, and the ongoing preference of certain schools for remote learning options. It is imperative that all educational institutions proactively anticipate unforeseen circumstances, encompassing not only weather-related disturbances but also the broader realm of potential future incidents. This study examined the applicability of offline mobile applications for modules and learning packs. The study employed a descriptive-analytic design which included 2,456 students based on web-based monitoring of offline mobile app installation and 189 teachers who completed the questionnaire on mobile application applicability. In the fourth quarter of 2023-2024, kindergarten to junior high school students and schools without modules and learning packets in the District of Cardona. Offline mobile applications allow students to learn at their own pace and in different situations. These offline mobile applications also improve educational accessibility, engagement, and usability. The impact of technological advancements on the future of education is apparent, with offline mobile applications positioned to play a pivotal role in determining this trajectory.